Altered Hemorheology in Fontan Patients in Normoxia and After Acute Hypoxic Exercise - Härtel, Julian Alexander; Müller, Nicole; Herberg, Ulrike; Breuer, Johannes; Bizjak, Daniel Alexander; Bloch, Wilhelm; Grau, Marijke (Frontiers in Physiology, 2019)
Background: The Fontan circulation is a unique palliation procedure for several congenital heart defects. Impaired exercise capacity has previously been demonstrated in these patients and also a higher risk for cardiopulmonary mortality. Hemorheology was shown to affect cardiopulmonary capacity and in turn to be affected by regular exercise and hypoxia but none of these have been investigated in Fontan patients so far. The aim of this study was to detect general differences in hemorheology in normoxia as well as possible altered hemorheological responses to hypoxia exposure and hypoxic exercise between Fontan patients and healthy controls. Methods and Findings: 26 Fontan patients and 20 healthy controls performed an acute exercise test on a bicycle ergometer under hypoxia with ambient 15.2% oxygen saturation. Blood samples were taken at rest in normoxia (T0), at rest in hypoxia (T1), after maximum exhaustion in hypoxia (T2) and after 50 minutes recovery in normoxia (T3). Hemorheological and blood parameters were investigated. Additionally, arterial stiffness was tested at T0. Red blood cell (RBC) deformability, NOx, EPO concentration, RBC count, hemoglobin concentration and hematocrit were significantly increased in Fontan patients compared to controls. Same was observed for arterial stiffness. No changes were observed for RBC aggregation, fibrinogen concentration, free radical levels and VEGF. Hypoxia exposure did not change parameters, whereas exercise in hypoxia increased aggregation and hct significantly in both groups. Fontan patients showed significantly increased aggregation-disaggregation balance compared to controls. Conclusions: Acute hypoxia exposure and exercise under hypoxia might have similar impact on hemorheology in Fontan patients and controls and was clinically well tolerated. Nevertheless, exercise alters aggregation and possibly hemodynamics which requires special attention in Fontan patients.